Incidence and Implications of Culture-Positive Corneoscleral Rims in Corneal Transplantation - Meeraalam Z; Alreshidi SO; ALBalawi HB; Alali NM; Hashem F; Kirat OM (Infection and Drug Resistance)
Zuheer Meeraalam,1 Shaker O Alreshidi,2 Hani B ALBalawi,3 Naif M Alali,3 Faris Hashem,3 Omar M Kirat4 1Ophthalmology Department, Prince Sultan Military Medical City, Riyadh, Saudi Arabia; 2Ophthalmology Division, Department of Surgical Specialties, College of Medicine, Majmaah University, Majmaah, Saudi Arabia; 3Division of Ophthalmology, Department of Surgery, Faculty of Medicine, University of Tabuk, Tabuk, Saudi Arabia; 4Anterior Segment Division, King Khaled Eye Specialist Hospital, Riyadh, Saudi ArabiaCorrespondence: Hani B ALBalawi, Division of Ophthalmology, Department of Surgery, Faculty of Medicine, University of Tabuk, Tabuk, 71491, Saudi Arabia, Email hb.albalawi@ut.edu.saBackground: Corneal transplantation is a critical procedure for restoring vision affected by different corneal pathologies. However, postoperative infections threaten graft survival, particularly microbial keratitis and endophthalmitis.Objective: This study aims to evaluate the incidence of culture-positive corneoscleral rims (CPCR) among transplanted corneas at a tertiary eye hospital and explore its association with death-preservation and preservation-surgery times.Methods: A retrospective analysis of keratoplasty surgeries performed in 2015 was conducted, involving 603 cases meeting the study criteria.Results: The incidence of CPCR was found to be 4.6%, predominantly bacterial (68%), with Methicillin-resistant Staphylococcus epidermidis (MRSE) being the most common isolate, followed by fungal (32%) species, notably Candida. However, none of the cases developed subsequent keratitis or endophthalmitis post-transplantation. Statistical analysis revealed no significant association between CPCR occurrence and death-preservation or preservation-surgery times.Conclusion: The study underscores the reduced impact of contaminated CPCR on graft outcomes, advocating for targeted fungal culturing, intraoperative practices to mitigate post-transplant infections, and maintaining current prophylactic antibiotic regimens, such as optisolGS ™, which contains streptomycin and gentamicin.Keywords: corneal transplant, keratitis, endophthalmitis, infection, bacterial keratitis